The Role of Interactive E-Books in Enhancing Science Literacy: A Review of Studies from 2015 to 2024 - Kurniadin, Muh. Zikron (Balai Publikasi Indonesia, 2025)
This study explores the role of interactive e-books in supporting science literacy through bibliometric analysis using Publish or Perish, VOSviewer, and Dimensions tools. By utilizing overlay, density, and network visualizations, this study identifies key research trends, relationships between concepts, and term frequency densities in the literature related to interactive e-books. The results of the analysis show that publications related to interactive e-books in science literacy have increased significantly during the COVID-19 pandemic, with articles and book chapters being the most dominant forms of publication. These findings suggest that interactive e-books not only support more flexible science learning but also enable the integration of digital technologies to improve critical thinking skills and understanding of scientific concepts across a range of subject areas, including health and agricultural sciences.